The Effect of Work Wages on Employee Performance At PT. Wilmar Food - Marsinah, Marsinah; R.A Rodia Fitri Indriani (CV. Picmotiv, 2023)
Human resources play an essential role in a company, because the human factor (employees) is the main driver in every activity in the company, because employees who carry out company activities start from planning, and implementing, to controlling every activity and activity of the company. wages on employee performance at PT. Wilmar Food Jambi. This research is descriptive quantitative research. The population in this study are employees who work at PT. Wilmar Food Jambi. Sampling with saturated sampling technique, with a sample of 18 respondents. The data collection method in this study used a questionnaire. This study's data analysis method used descriptive statistics using scores, percentages, and tables. Based on the analysis that has been done, it can be concluded that wages have an effect on employee performance. This can be seen from the average percentage on the wage variable as much as 85% positive response and on the employee performance variable as much as 97% positive response given by the respondent. This shows that the better the level of remuneration by the company, the better the employee performance. The results of this study indicate that wages have an effect on employee performance